Measurement of narcissism: From classical applications to modern approaches - Rogoza, Radosław; Żemojtel-Piotrowska, Magdalena; Campbel, William Keith (Studia Psychologica: Theoria et praxis, 2018)
Different conceptions of narcissism exist within the literature such as grandiose, vulnerable, pathological, collective, and communal, each of which can be measured using self-report measures. Within the current paper, we review and discuss most of the existing measures of these different trait (i.e., non-clinical) narcissism constructs. This includes an examination of their underlying theoretical foundations and an evaluation of the scale construction process. We start our review from the one-dimensional measures of grandiose and vulnerable narcissism such as the Narcissistic Personality Inventory, the Hypersensitive Narcissism Scale, the Dark Triad Dirty Dozen, the Short Dark Triad, the Narcissistic Grandiosity Scale, the Narcissistic Vulnerability Scale, and the Single Item Narcissism Scale. Then, we introduce the multidimensional measures to study narcissism such as the Narcissistic Admiration and Rivalry Questionnaire, the Five Factor Narcissism Inventory, and the Pathological Narcissism Inventory. The r view concludes by presenting measures of understudied narcissistic constructs such as the Communal Narcissism Inventory and the Collective Narcissism Scale. In general, using one-dimensional scales might provide important insights into the general underpinnings of narcissistic personality, however assessment via multi-dimensional tools better reflects its complex nature.